Dynamic improvement for phase-shift LLC resonant converter based on disturbance observer. (March 2023) - Chen, Wenzhe; Liu, Kangli; Zhao, Jianfeng; Jin, Cheng
Abstract: LLC resonant converters have been widely used in DC/DC conversion because of their high efficiency. However, the converters are highly nonlinear, making it hard to use typical linear control methods. This paper proposes a disturbance-observer-based control approach, which achieves better performance compared with the conventional PI controller. First, according to the extended describing function (EDF) method, the small-signal model of the phase-shift LLC resonant converter is established, which is further simplified to a third-order system. Then, the disturbance-observer-based control is presented, which incorporates a disturbance observer (Dob) to estimate the uncertain effects resulting from external disturbances, circuit parameters variation and model mismatch, and compensate for them in a feedforward way. The main advantage of this control structure is that it can improve the stability and dynamic response simultaneously, where the Dob optimizes the dynamic responses and the PI controller is designed to satisfy the stability requirement. Finally, a 600 W simulation model is built in MATLAB/Simulink to verify the proposed control method, whose superiority over the classic PI controller is proved by the simulation results.